The Role of Instagram “@Cidulang_Geresik” Account in Building an Intelligent Community: Implementation and Obstacles - Dhita Shaleh Farisya; Sri Wulandari; Dian Andriany (Athena: Journal of Social, Culture and Society, 2026)
This study purpose to analyze the function, role, and influence of Instagram account @cidulang_geresik in providing information to build a smart community. This study uses a qualitative approach through interviews with the admin of the Instagram account @cidulang_geresik. The results show that the function of Instagram @cidulang_geresik is optimal by utilizing features such as feeds, stories, highlights, and reels to disseminate information about hamlet or village activities. The Instagram account @cidulang_geresik has a cognitive, emotional, and behavioral influence on residents. The role of the Instagram account @cidulang_geresik effectively carries out two-way communication functions and strengthens social relationships. Implementation is carried out through regular content uploads, the use of photos and videos, the use of story and live features, and collaboration with village officials in disseminating public information. However, there are obstacles such as the limited number and availability of admins, unequal digital literacy among residents, inconsistent quality of content production, and internet network constraints that hinder access to information. Overall, the Instagram account @cidulang_geresik shows a positive contribution as a village communication and information medium. Through optimal functions, influence, and roles, Instagram can be used to build a smart community so as to improve the quality of life.